A STEGANOGRAPHY LEAST SIGNIFICATION BITS (LSB) TECHNIQUE FOR HIDE TEXT DATA ENCRYPTION WITHIN IMAGE - Riyadh Alnajih Alsayih; Muhamad Qomaruddin; Imam Much Ibnu Subroto; Suryani Alifah (Universitas Islam Sultan Agung, 2020)
With the development of means of communication and the exchange of information over the Internet, and with the development of hacking operations, intruders became able to view, and change information, so the need to find means to preserve privacy and information exchange arose. Cryptography and steganography had a prominent role in this field Encryption distorts the message and steganography hides the message's presence. In this paper, the proposed system uses both steganography and cryptography to provide a double layer of security. In cryptography, we use both a substitution and RSA algorithm to encrypt the message. In steganography, we used LSB technology with a stego key to embed data in the image, all of this to improve data security. A scale of Mean Square Error (MSE) and a scale of peak signal-to-noise ratio (PSNR) assessed system performance. The results showed that the image quality is good, and it is difficult to notice any difference between it and the original image. The results of both MSE and PSNR were good, as the PSNR value was more than 56.